Scale insect species names combined with the genus name Chermes Linnaeus (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, D. J. (Zootaxa, 2015)
Species names in the scale insects that have been combined with the genus name Chermes Linnaeus, 1758, are listed. This list supplements a list published already for the Sternorrhyncha but that was restricted to names of species that had been described originally in the genus. The present list includes, in addition, all species names in the scale insects that have been combined with the name Chermes.